IMPLEMENTASI KEPEMIMPINAN SIFAT KEPALA SEKOLAH DALAM MENGELOLA TANTANGAN SIFAT GURU DI SEKOLAH DASAR: Indonesia - Antonius Ferrian Dwi Prasetyo; Yari Dwikurnaningsih; Herry Sanoto (STKIP Subang, 2026)
This study aims to analyze the implementation of trait-based leadership of school principals in managing teachers’ trait-related challenges in elementary schools. The research employed a qualitative descriptive approach with a literature study design. Data were obtained from scientific journals, books, and relevant research reports published in the last ten years. Data analysis was conducted using interactive analysis techniques, including data reduction, data display, and conclusion drawing. The findings indicate that principals’ leadership traits such as integrity, emotional stability, openness, decisiveness, and empathy significantly influence their effectiveness in managing diverse teacher characteristics. Teachers’ trait-related challenges include resistance to change, low adaptability, lack of collaboration, and varying professional commitment. Effective leadership implementation is reflected in the principal’s ability to model positive character, build constructive communication, and foster a supportive school climate. The study concludes that trait-based leadership remains relevant in elementary school management, particularly when integrated with contextual and relational approaches.